A Study of Application Layer Paradigm for Lower Layer Energy Saving Potentials in Cloud-Edge Social User Wireless Image Sharing - Wang, Wei; Sohraby, Kazem (EAI Endorsed Transactions on Energy Web, 2015)
Energy saving becomes critical in modern cloud wireless multimedia and mobile communication systems. In this paper we propose to study a new paradigm named application layer Position-Value diversity for wireless image sharing for cloud-edge communications, which has significant energy saving potentials for modern wireless networking systems. In this new paradigm, saving energy is achieved by looking into application layer imaging traffic, in stead of MAC-PHY protocols at lower layers, and partitioning it into important positions and unimportant values. This paradigm could be integrated to existing wavelet-based tree compression, and truncation of image bit streams could be performed with regards to wireless communication energy budget estimation. Simulation results demonstrated that there are significant potentials of communication energy efficiency gain and Quality of Experience (QoE) enhancement in wireless image communication systems.
Keywords: wireless multimedia transmission; energy efficiency